Equations for gap-spanning design of underground cast iron pipes lined with thermosetting polymeric liners. (January 2022) - Fu, Guoyang; Shannon, Benjamin; Azoor, Rukshan; Deo, Ravin; Kodikara, Jayantha
Highlights: Effect of circumferential defects on the performance of lined pipes is studied. Equations for gap-spanning design of lined cast iron pipes are derived. Reducing the ratio of pipe modulus to liner modulus increases liner max. stress. Increasing friction coefficient increases the liner max. stress. Reducing the ratio of liner thickness to diameter increases liner max. stress. Abstract: Polymeric spray and cured-in-place-pipe liners have attracted the attention of water utilities as alternatives for renovation of deteriorated cast iron pipes. Circumferential defects, in the form of existing gaps, ring fractures or failed joints, may exist in cast iron pipes and they may significantly influence the performance of the lined pipes under applied loads. Literature review showed that limited research has been conducted to investigate the effect of circumferential defects. This paper aims to comprehensively examine the mechanical performance of polymer lined cast iron pipes with circumferential defects, using finite element analyses, and derive equations based on the finite element results for engineering design. Three different failure modes, namely, lining through existing gaps in pressurized host pipes, formation of gaps for pressurized lined pipes subjected to axial movements, and pressurized lined pipes with ring fractures under bending, are comprehensively studied. After validation of the developed numerical models for each of the failure modes, parametric studies were conducted considering different pipe properties, liner properties, loading conditions and interface properties. Equations were then derived based on the numerical results using non-linear regression for the three failure modes to facilitate the use of the results in practice. It was found from this study that for all three modes a reduction in the ratio of the cast iron pipe modulus to liner modulus will result in an increase in the normalized maximum stress, which is defined as the ratio of the maximum stress to internal pressure in the liner. This effect is most significant for formation of gaps for pressurized lined pipes subjected to axial movements and pressurized lined pipes with ring fractures under bending. It was also found that by increasing the friction coefficient or reducing the ratio of liner wall thickness to pipe diameter, the normalized maximum stress in the liner increases. Among the three failure modes, the normalized maximum stress in the liner for formation of gaps for pressurized lined pipes subjected to axial movements was affected the most.